2003
DOI: 10.2486/indhealth.41.287
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Model to Study Reproductive Toxicity of Chemicals using Induced Ovulation in Immature F344 Rats.

Abstract: We investigated a simple method using induced ovulation in immature rats to detect ovarian injury due to chemicals. We investigated the influence of di-(2-ethylhexyl) phthalate (DEHP) on ovulation induced by equine chorionic gonadotropin (eCG) in immature F344 rats. Single injections of 15 and 30 iu eCG induced ovulation in 4 of 6 rats and in all of 4 rats, respectively. The mean number of ovulated ova was 12.7 in the 15 iu eCG group and 8.0 in the 30 iu group. When rats received 4 daily doses of DEHP at 500 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…It has long been known that follicles of 4-to 8-week-old lambs are particularly sensitive to gonadotropin administration using protocols developed for adult animals (Worthington & Kennedy 1979, Armstrong et al 1994, Ptak et al 1999. On the other hand, ovarian stimulation has proved to be a simple and useful tool to detect alterations in rodent reproductive organs and to study likely changes in the mechanisms of hormonal action induced by certain substances (Sekiguchi et al 2003). In this study, we applied a protocol of oFSH-ovarian stimulation in prepubertal lambs and demonstrated that early postnatal exposure of BPA or DES impaired the ovarian functional response to oFSH treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has long been known that follicles of 4-to 8-week-old lambs are particularly sensitive to gonadotropin administration using protocols developed for adult animals (Worthington & Kennedy 1979, Armstrong et al 1994, Ptak et al 1999. On the other hand, ovarian stimulation has proved to be a simple and useful tool to detect alterations in rodent reproductive organs and to study likely changes in the mechanisms of hormonal action induced by certain substances (Sekiguchi et al 2003). In this study, we applied a protocol of oFSH-ovarian stimulation in prepubertal lambs and demonstrated that early postnatal exposure of BPA or DES impaired the ovarian functional response to oFSH treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of this procedure to investigate female reproductive toxicity certainly simplifies and reduces the time-consuming properties of routine experiments (such as evaluation of the estrous cycle, spontaneously ovulated ova, etc.) and allows the development of toxicological procedures to elucidate the mechanisms of toxicants, which impair the female reproductive system (Sekiguchi et al 2003). Based on these reasons, we selected the ovarian response to an exogenous gonadotropin treatment as a tool to study ovarian functionality in immature lambs neonatally exposed to xenoestrogens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co., Ltd., Japan) at a dose of 15 iu in 0.15 ml saline injected intramuscularly (im) at 25 d of age to intact females and at 28 d of age to hypox females followed by 15 iu hCG (Teikoku Hormone) in 0.15 ml saline injected intraperitoneally (ip) at 27 or 30 d of age, 56 or 72 h after the eCG injection. All rats were sacrificed by decapitation at 28 or 31 d of age, at 72 h after the eCG injection 16) , and the ovaries and uteri were weighed after removing the fat and connective tissue. Ova shed into oviducts were collected and counted 16) .…”
Section: Animals and Experimental Designsmentioning
confidence: 99%
“…In our previous study, subcutaneous injections of 500 mg/kg of DEHP administered to immature F344 rats tended to suppress superovulation induced by a single injection of eCG 16) . In the present study, in order to determine the exact effects of DEHP on reproductive function, the ability of eCG and hCG to induce superovulation in DEHP-treated rats was estimated, and we also investigated whether thyroid hormone is involved in the ovarian toxicity of DEHP.…”
Section: Introductionmentioning
confidence: 99%